A qualitative study on pharmacy policies toward over-the-counter syringe sales in a rural epicenter of US drug-related epidemics - Monica Fadanelli; Hannah L. F. Cooper; Patricia R. Freeman; April M. Ballard; Umed Ibragimov; April M. Young (BMC, 2022)
Abstract Background Expanding access to sterile syringes in rural areas is vital, as injection-related epidemics expand beyond metropolitan areas globally. While pharmacies have potential to be an easily accessible source of sterile syringes, research in cities has identified moral, legal and ethical barriers that preclude over-the-counter (OTC) sales to people who inject drugs (PWID). The current study builds on prior urban-based research by elucidating (1) pharmacy OTC policies and (2) pharmacists' rationale for, and barriers and facilitators to, OTC syringe sales in a US rural area hard hit by drug-related epidemics. Methods We conducted 14 semi-structured interviews with pharmacists recruited from two Eastern Kentucky health districts. Interview domains included experiences with, and attitudes toward, selling OTC syringes to PWID. Constructivist grounded theory methods were used to analyze verbatim transcripts. Results Most pharmacists operated "restrictive OTC" pharmacies (n = 8), where patients were required to have a prescription or proof of medical need to purchase a syringe. The remainder (n = 6) operated "open OTC" pharmacies, which allowed OTC syringe sales to most patients. Both groups believed their pharmacy policies protected their community and pharmacy from further drug-related harm, but diverging policies emerged because of stigma toward PWID, perceptions of Kentucky law, and belief OTC syringe sales were harmful rather than protective to the community. Conclusion Our results suggest that restrictive OTC pharmacy policies are rooted in stigmatizing views of PWID. Anti-stigma education about substance use disorder (SUD), human immunodeficiency virus (HIV), and Hepatitis C (HCV) is likely needed to truly shift restrictive pharmacy policy.